Orbital Metastasis of Undifferentiated/Anaplastic Thyroid Carcinoma. Issue 5 (September 2015) - Gupta, Divakar; Chappell, Michael; Tailor, Tina D.; Keene, C. Dirk; Moe, Kris; Jian-Amadi, Arash; Chang, Shu-hong
<x xml:space="preserve">Abstract</x> A 52-year-old woman presented with decreased vision, diplopia, esotropia, proptosis, and right orbital pain. Clinical examination was suspicious for an orbital mass and additionally revealed a thyroid gland mass. Imaging studies showed an enhancing mass within the right lateral rectus muscle and a heterogeneous mass in the left lobe of the thyroid gland. Excisional biopsies of the thyroid and orbital lesions were consistent with metastatic undifferentiated/anaplastic thyroid carcinoma. This represents the first reported case of undifferentiated/anaplastic thyroid carcinoma metastatic to the orbit.